Use of Tourniquet Under Sedation Anesthesia or the Walant Techniques in Bilateral Carpal Tunnel Surgery: A Comparative Analysis - ALBAYRAK, Mehmet; UĞUR, Fatih (Medical Records - International Medical Journal, 2023)
Aim: The objective of the study was to compare the outcomes and patient satisfaction of two different anesthesia techniques; wide-awake-local anesthesia-no tourniquet (WALANT) and sedation anesthesia with a tourniquet, in open carpal tunnel release surgery for bilateral cases. Material and Methods: The study included 57 patients (41 female, 16 male) who underwent carpal tunnel release surgery between January 2016 and September 2021. The files were retrospectively evaluated and included in the present study. Patient evaluations were conducted using QuickDASH and Michigan Hand Outcomes Questionnaire scores before surgery, on the 15th day after suture removal, and at six months postoperatively. Surgical duration and complications were also recorded. Statistical analyses were performed to compare the outcomes between the two groups. Results: Both QDash and MHQ scores were analyzed for anesthesia effects on hands. The study's reliability was ensured by an 85% statistical power, 95% confidence level, and p
Keywords: Carpal Tunnel Syndrome; Sedation; Tourniquet; Ortopedi; Orthopaedics; 3. Good health